2010
DOI: 10.1038/cdd.2010.65
|View full text |Cite|
|
Sign up to set email alerts
|

c-FLIPL enhances anti-apoptotic Akt functions by modulation of Gsk3β activity

Abstract: Akt is a serine-threonine kinase that has an important role in transducing survival signals. Akt also regulates a number of proteins involved in the apoptotic process. To find new Akt interactors, we performed a two-hybrid screening in yeast using full-length Akt cDNA as bait and a human cDNA heart library as prey. Among 200 clones obtained, two of them were identified as coding for the c-FLIP L protein. c-FLIP L is an endogenous inhibitor of death receptor-induced apoptosis through the caspase-8 pathway. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…It was first discovered as an oncogene within the mouse leukemia virus [31,32] and as a homolog of protein kinase C [33]. Thereafter, there have been many exciting breakthroughs elucidating the mechanism of upstream regulation of AKT [34-36]. AKT promotes cell survival through the phosphoinositide 3-kinase (PI3K) pathway.…”
Section: Resultsmentioning
confidence: 99%
“…It was first discovered as an oncogene within the mouse leukemia virus [31,32] and as a homolog of protein kinase C [33]. Thereafter, there have been many exciting breakthroughs elucidating the mechanism of upstream regulation of AKT [34-36]. AKT promotes cell survival through the phosphoinositide 3-kinase (PI3K) pathway.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, we focused on AKT, a serine-threonine kinase that prevents apoptosis induced by various stress conditions by interacting with apoptotic modulators such as BAD [39], Caspase-9 [40], FOXO3 [41] and Bcl-w [42]. AKT has previously been shown to interact with c-FLIP L, which inhibits its function and blocks its ability to activate the substrate GSK3β [30]. Interestingly, several studies point to the involvement of AKT in ER stress response.…”
Section: Discussionmentioning
confidence: 99%
“…C. Quintavalle et al [30] demonstrated that c-FLIP interacts with AKT and inhibits its ability to bind to and regulate its substrate GSK3β, probably by sequestering AKT and limiting its access to the target protein. Interestingly, we have previously demonstrated that a pool of c-FLIP proteins localizes at ER [22].…”
Section: C-flip−/− Cells Display Greater Akt Activation Than Wtmentioning
confidence: 99%
See 1 more Smart Citation
“…Further characterizing the CaM/c-FLIP interaction may provide a new therapeutic target for developing anticancer therapies [117]. By co-immunoprecipitation experiments, Quintavalle et al [118] demonstrated that the interaction between Akt and c-FLIPL enhances the anti-apoptotic functions of Akt by modulating Gsk3-β activity. Moreover, these authors have shown that c-FLIPL overexpression interferes with Gsk3-β phosphorylation levels and induces resistance to TRAIL in cancer cells.…”
Section: C-flip Activates Cytoprotective and Proliferation Pathwaysmentioning
confidence: 99%